Handbook of sample preparation for scanning electron microscopy and x-ray microanalysis - Echlin, Patrick (Springer, 2017)
This Handbook is a complete guide to preparing a wide variety of specimens for the scanning electron microscope and x-ray microanalyzers. Specimens range from inorganic, organic, biological, and geological samples to materials such as metals, polymers, and semiconductors which can exist as solids, liquids and gases. While the Handbook complements the best-selling textbook, Scanning Electron Microscopy and X-Ray Microanalysis, Third Edition, by Goldstein, et al., it is entirely self-contained and describes what is needed up to the point the sample is put into the instrument. Photomicrographs of each specimen complement the many sample preparation "recipes." Additional chapters describe the general features of specimen preparation in relation to the different needs of scanning electron microscopes and x-ray microanalyzers, and an appendix covers chemicals and equipment applicable to any of the recipes. This practical Handbook is an essential reference for anyone who uses these instruments. It assumes only an elementary knowledge of preparation techniques but also serves as an authoritative guide for more experienced microscopists.